Auditoría en seguridad vial variante Condina ruta nacional 29RSD, desde el K 0+000 hasta el K 6+500 en el departamento de Risaralda (2022)
The present work contains the realization of a Road Safety Audit on the Variant Condina road k 0+000 to K 6+500 National Route 29RSD; the variables analyzed are the vehicular containment barriers, horizontal and vertical signaling, and the geometric design of the road, to establish if any of them is the cause of accidents for the actors who travel along the aforementioned road.